Upaya Peningkatan Pengetahuan Dan Keterampilan Ibu Bayi Tentang Makanan Pendamping Air Susu Ibu (Mp-Asi) di Posyandu Singosari Banyuanyar Surakarta - Erlyn Hapsari; Aryanti Setyaningsih; Christiani Bumi P; Erinda Nur Pratiwi (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Complementary foods for breast milk (MP-ASI) is food or drink that contains nutrients other than breast milk, this is because breast milk is only able to meet two-thirds of the baby's needs at 6-9 months of age, and at 9-12 months it fulfills half of the baby's needs. Age under two years is a very important period as well as a critical period in the process of growth and development of babies both physically and intellectually, therefore every baby and child aged 6-24 months must obtain nutritional intake according to their needs. The survey results show that one of the causes of growth and development disorders for babies and children aged 6-24 months in Indonesia is the low quality of complementary foods and not according to the parenting style given so that some nutrients cannot meet the needs, especially energy and micronutrients, especially iron. (Fe) and Zinc (Zn). The purpose of this community service is that after receiving counseling, it is hoped that the baby's mother at Singosari Banyuanyar Surakarta Posyandu can be understanding about complementary foods so that the baby's nutrition is fulfilled and can make complementary foods themselves. This community service activity got results, namely counseling followed by 15 mommies which were held on July 17, 2020, at Singosari RW 05 Posyandu. This community service activity received a good response. Posyandu babies' mothers know more about complementary foods. This can be seen from the results of the question and answer, where before counseling about complementary foods, posyandu babies do not understand complementary foods, but after counseling about complementary breastfeeding, posyandu babies become more aware of complementary foods with value. the average knowledge of complementary foods increased by 80%.